2016
DOI: 10.1007/s00338-016-1492-2
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on the spatial distribution and morphology of the Halimeda bioherms of the Great Barrier Reef, Australia

Abstract: Halimeda bioherms occur as extensive geological structures on the northern Great Barrier Reef (GBR), Australia. We present the most complete, high-resolution spatial mapping of the northern GBR Halimeda bioherms, based on new airborne lidar and multibeam echosounder bathymetry data. Our analysis reveals that bioherm morphology does not conform to the previous model of parallel ridges and troughs, but is far more complex than previously thought. We define and describe three morphological sub-types: reticulate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…A distinct unit boundary identified in RBR_5 at 24.9 m, below PMSL, represents the antecedent surface of the pre-LIG reef, presumed to be MIS-7 in age (Webster andDavies, 2003, Braithwaite andMontaggioni, 2009). Immediately above this boundary This transition from shallow to deep coralgal assemblages coincides with an increase in Halimeda-rich grainstone, similar in character to Holocene deposits found behind the northern Ribbon reefs of the modern GBR below 20 m depth (Orme et al, 1978, Marshall and Davies, 1988, McNeil et al, 2016. These results are in good agreement with Braga and Aguirre (2004) and Webster and Davies (2003) suggesting the reef was at or close to sea level.…”
Section: Microfacies Analysismentioning
confidence: 85%
“…A distinct unit boundary identified in RBR_5 at 24.9 m, below PMSL, represents the antecedent surface of the pre-LIG reef, presumed to be MIS-7 in age (Webster andDavies, 2003, Braithwaite andMontaggioni, 2009). Immediately above this boundary This transition from shallow to deep coralgal assemblages coincides with an increase in Halimeda-rich grainstone, similar in character to Holocene deposits found behind the northern Ribbon reefs of the modern GBR below 20 m depth (Orme et al, 1978, Marshall and Davies, 1988, McNeil et al, 2016. These results are in good agreement with Braga and Aguirre (2004) and Webster and Davies (2003) suggesting the reef was at or close to sea level.…”
Section: Microfacies Analysismentioning
confidence: 85%
“…Increased upwelling of cool, nutrient-rich water via shelf break upwelling or tidal jetting in the northern and central regions of the GBR at ~11 ka has been considered responsible for supporting the construction of large Halimeda bioherms behind reef platforms on the mid-outer shelf (Searle and Flood, 1988, Wolanski et al, 1988, Hopley et al, 2007, McNeil et al, 2016. However, only small accumulations of Halimeda have been identified within the Holocene platform reefs themselves with no regional variations in Halimeda abundance in the northern, central or southern reefs Hopley, 1983, Hopley et al, 2007).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Coral reefs account for approximately 35,000 km 2 or 10% of the area of the Great Barrier Reef Marine Park [40]. Similar comments can be made about the less studied inter-reefal soft sediment habitats, and the 6000 km 2 of Halimeda meadows and bioherms that have received very little scientific attention in tropical coastal and shallow shelf waters [41]. While cross shelf transects have been carried out along the Great Barrier Reef, to study the impact of trawling on these inter-reefal habitats infauna was not identified and only gross classifications of epifaunal communities were made [42].…”
Section: Ecological Studiesmentioning
confidence: 63%